Youthful Perspectives In Efl: The First Year Students’ Point Of View On English Subject - Cut Mawar Helmanda; Siti Safura (Simpati, 2023)
This study on students’ points of view on English subject was conducted with the first year students at SD 1 Muhammadiyah Banda Aceh. The aim of this study was to address a main question called What are the students’ points of view on English subject?. In addition to this, finding out the students’ point of view on English subject was the aim of this study. The qualitative research employed interviews as the instrument. The interviews were conducted to explore participants’ experiences, perspective, and difficulties regarding the English language. The collected data were analyzed using descriptive analysis. The findings revealed that the majority of students responded positively to the questions. However, students confirmed that English is a challenging subject to learn. In conclusion, the study indicates that students hold a positive point of view on the English subject. The majority of SD 1 Muhammadiyah Banda Aceh first year students have favorable opinions about English subject.